Dexoris ruzzieri sp. nov. (Coleoptera: Lycidae), a new net-winged beetle from Ivory Coast - Bocak, Ladislav (Zootaxa, 2018)
Dexoris ruzzieri sp. nov. is described from Mt. Tonkoul, Ivory Coast. This is the second record of a Dexoris species from the regions west of the Dahomey Gap. The unique specimen is available due to rareness of Dexoris Waterhouse, 1878. All Dexoris, including D. ruzzieri sp. nov., are only known from male specimens and despite the growing number of known species, females remain unknown.